Genetic Diversity of the Vulnerable Pangasius sanitwongsei using Microsatellite DNA and 16S rRNA - Na-Nakorn, Uthairat; Sukmanomon, Srijanya; Poompuang, Supawadee; Saelim, Panya; Taniguchi, Nobuhiko; Nakajima, Masanishi (Journal of Fisheries and Environment, 2009)
Sixty-six Pangasius sanitwongsei were collected from five sites, namely Chiangkhong District, Chiangrai Province (CR; N = 1, for mt-DNA study only), Muang District, Nakornphanom Province (NP-1; N = 4), Tatphanom District, Nakornphanom Province (NP-2; N = 41), Khongjiam District, Ubonratchathani Province (UR; N = 10) and Koagsrisuphan District, Sakonnakorn Province (SN; N = 10). Seven microsatellite primers developed from Pangasianodon gigas were used. The results indicated very low genetic variation of P. sanitwongsei (A=1.43 - 3.O; H0 = 0.11 - 0.30; He= 0.12 - 0.36). Although the least diverse population (SN, A= 1.43; H0= 0.11; He = 0.12) might be of hatchery origin, the genetic variation of the other populations was still low. Population structuring was significant (FsT = 0.190). The genotypic differentiation was significant between SN and the others. Genetic distance was between 0.0952 - 0.4872. The sequences of the 571 bp16S rRNA gene region revealed a total of 6 haplotypes (CR = 1; NP-1 = 1; NP-2 = 5; SN = 2; UR = 1) with 8 variable sites comprising 5:3 transitional to transversional mutation. Haplotype and nucleotide diversity varied from 0 (NP-1 and UR) to 0.3556 (SN) and 0 (CR, NP-1, UR) to 0.0006 (NP-2, SN), respectively. The status of P. sanitwongsei as an endangered species was validated. At least two evolutionary significant units (ESU) were identified i.e. NP-1+NP-2 and UR. Samples of SN were mainly of hatchery origin and closely related to CR as evidenced by 16S rRNA.